(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The prolific plant diversity of Uttarakhand hills has provided an initial lead to the local people to look for various plant species for the purpose of food, medicine, spices and perfumes. Medicinal plants found in Pauri district at Yamkeshwar block Uttarakhand, India have resulted in the documentation of medicinal, aromatic and spice plant species. These species were distributed over various life forms, like tree, shrub and herbaceous forms. The plants species were collected and arranged in their botanical name family, Sanskrit name, local name and their habit pattern. The leaves root, stem bark and whole plants were the mostly used. The traditional knowledge of medicinal plants gathered from local healers at Yamkeshwar block transmitted orally one generation to another generation but not documented. Now new generation is not interested in traditional knowledge of medicinal plants due to modernization, so there is an urgent need to document ethnomedicinal plants before the knowledge become extinct. Conservation and sustainable utilization of these valuable medicinal plant species is essential to protect the traditional knowledge regarding plants and plant based healing practices. In this article made an effort to document such information, especially the plants found in that region and use of plants for medicine, and made an effort to enlist the medicinal plants mentioned in Bhavaprakash Nighantu.